2015
DOI: 10.3892/mmr.2015.4557
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-1246 promotes growth and metastasis of colorectal cancer cells involving CCNG2 reduction

Abstract: Colorectal cancer (CRC) is the third most common cancer type and the fourth leading cause of cancer‑associated mortality worldwide. MicroRNA (miR)‑1246 is involved in differentiation, invasion, metastasis and chemoresistance of certain types of tumor cells. CCNG2 encodes an unconventional cyclin homolog, cyclin G2 (CycG2), associated with growth inhibition, which correlated significantly with lymph node metastasis, clinical stage, histological grade and poor overall survival in numerous cancer types. To invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
42
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(49 citation statements)
references
References 26 publications
7
42
0
Order By: Relevance
“…Therefore, we excluded miR-342–3p from further investigation and continued exploring the functional mechanism of miR-1246 . Recently, extracellular miR-1246 has been reported to promote lung cancer proliferation and enhance radioresistance2728. Importantly, in our study, we found that DENND2D is a direct target of miR-1246 and demonstrated a gene expression pattern that resembled that of HOC313-LM cells (Fig.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Therefore, we excluded miR-342–3p from further investigation and continued exploring the functional mechanism of miR-1246 . Recently, extracellular miR-1246 has been reported to promote lung cancer proliferation and enhance radioresistance2728. Importantly, in our study, we found that DENND2D is a direct target of miR-1246 and demonstrated a gene expression pattern that resembled that of HOC313-LM cells (Fig.…”
Section: Discussionsupporting
confidence: 67%
“…The most salient finding was a set of 11 miRNAs that are commonly upregulated in HOC313-LM cells at the cellular and exosomal level (Table 1). Based on these results, we focused on seven miRNAs, miR-17, miR-30a-3p, miR-30a-5p, miR-92a, miR-181a, miR-342–3p and miR-1246 , all of which have been reported as oncogenic miRNAs (oncomiRs)22232425262728. Using quantitative RT-PCR (qRT-PCR), we could validate the differential expression of six of these miRNAs (all except miR-92a ) in cells and exosomes (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, miR-1246 directly targets CCNG2 expression by binding to its 3′UTR. Many studies have evaluated the importance of exosomes in cancer progression [14, 15]; for instance, exosomes secreted by highly metastatic cells contribute significantly to cancer progression of poorly metastatic cells, which is consistent with the idea that cancer cells interact with each other through exosomes. We found that exosomes isolated from MDA-MB-231 cells could induce malignant features in HMLE cells by increasing their cell growth and cell invasion.…”
Section: Discussionsupporting
confidence: 53%
“…In addition, the correlation between miR‐1246 and the target gene CCNG2 still needs further study. Although the direct regulating relationship has been confirmed in oral, breast, pancreatic, and colorectal cancers we still need to clarify in LSCC.…”
Section: Discussionmentioning
confidence: 99%